On the Design of Running Gears with Radial Steering Wheel Sets - Oldrich Polach (Communications - Scientific letters of the University of Zilina, 2003)
Noise reduction of railway vehicles can be reached by suitable design of their bogies and running gears. Radial steering wheel sets avoid curve squeal. Besides they reduce lateral forces between the wheel and rail and their wear. Design principles for the development of interconnected self-steering wheel sets are introduced on examples of bogies for new articulated vehicles TEŽ and coupled single-axle running gears FEBA for commuter trains NSB Class 72 from Bombardier Transportation Winterthur.